2020
DOI: 10.12688/f1000research.26073.1
|View full text |Cite
|
Sign up to set email alerts
|

An R-based reproducible and user-friendly preprocessing pipeline for CyTOF data

Abstract: Mass cytometry (CyTOF) has become a method of choice for in-depth characterization of tissue heterogeneity in health and disease, and is currently implemented in multiple clinical trials, where higher quality standards must be met. Currently, preprocessing of raw files is commonly performed in independent standalone tools, which makes it difficult to reproduce. Here, we present an R pipeline based on an updated version of CATALYST that covers all preprocessing steps required for downstream mass cytometry analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Mass cytometry data preprocessing and automated cell classification Individual FCS files collected from each set of samples were pre-processed using a semi-automated R pipeline based on CATALYST to perform individual file concatenation, bead based normalization, compensation, debarcoding, and batch correction as previously Cell Reports Medicine 2, 100166, January 19, 2021 e4 Article ll OPEN ACCESS described. 76 During this process, inter-sample doublets were excluded based on the debarcoding scheme and intra-sample doublets were excluded based on DNA content. Spillover matrix for CyTOF compensation was assessed on all antibodies used in this study as previously suggested.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Mass cytometry data preprocessing and automated cell classification Individual FCS files collected from each set of samples were pre-processed using a semi-automated R pipeline based on CATALYST to perform individual file concatenation, bead based normalization, compensation, debarcoding, and batch correction as previously Cell Reports Medicine 2, 100166, January 19, 2021 e4 Article ll OPEN ACCESS described. 76 During this process, inter-sample doublets were excluded based on the debarcoding scheme and intra-sample doublets were excluded based on DNA content. Spillover matrix for CyTOF compensation was assessed on all antibodies used in this study as previously suggested.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Samples were pre-processed as described in the Appendix S1 and mass cytometry analysis was performed as previously described. 17,[60][61][62][63][64][65][66][67] A detailed description of the procedure is provided in the Appendix S1.…”
Section: Mass Cytometry Analysismentioning
confidence: 99%
“…Briefly, these analysis methods compare the distribution of expression values for each protein or gene between treatment groups for the subset of cells annotated as a given cell type. The optimal statistical test for this differential expression analysis remains an open question, although approaches based upon negative binomial tests are emerging as providing the best model of the distribution of the molecular abundances of both scRNA-seq (Hafemeister and Satija, 2019;Risso et al, 2018) and CyTOF data (Crowell et al, 2020;Nowicka et al, 2017). Standard pathway analysis tools can then be applied to determine the molecular pathways that were altered based upon the results of these differential expression analyses (Irizarry et al, 2009;Subramanian et al, 2005).…”
Section: Analysis Of Cell-type-dependent Molecular Changesmentioning
confidence: 99%